RESPON PEMIMPIN PEMBANGUNAN TERHADAP PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI DESA SARIBAKTI KECAMATAN PEUNDEUY KABUPATEN GARUT - Haerudin, Ae (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2016)
Abstract: The purpose of this study is to describe and analyze the influence of demographic background and attitudes of leadership on the response of leader development, describe and analyze the relationship between demographic background and attitudes of leadership, and to describe the percentage of responses development leader in PNPM-MPD in the village Saribakti District of Peundeuy Garut. This research uses descriptive method with quantitative approach through path analysis or path analysis. The tools used in this research is to use a questionnaire to describe and analyze the influence of demographic background and attitude development leader on the response to the PNPM-MPD, the relationship between demographic background and attitudes of leadership, as well as the percentage response of leader development on PNPM-MPD. The results of the study with a population of 50 people and a sample of 44 people with a confidence level of 95% indicates that the demographic background significant negative effect on the response of leader development, while the attitude of the leadership have a positive influence and significant impact on response development leader at 65%, and the influence from other factors not examined by 35%. Demographic background and attitudes of leadership has a positive relationship at 0.4861 with a level of relationship. 66% attitude and response development leader in PNPM-MPD is at a low level where the percentage of perception of 72.60%, 68.52% attitude and actions amounted to 28.53%, in terms of response seen development leader of perceptions and attitudes have a degree high, but at this stage of action into a very low level.Key Word: Development Leader Response, Community Empowerment,